2017
DOI: 10.9738/intsurg-d-16-00014.1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Surgical Difficulty in Laparoscopic Cholecystectomy for Acute Cholecystitis Performed Within 24 Hours After Hospital Admission

Abstract: The objective of this study was to identify preoperative factors predicting operative difficulty in patients who underwent laparoscopic cholecystectomy for acute cholecystitis within 24 hours after hospital admission. Many reports have described the superiority of performing laparoscopic cholecystectomy in the early phase of acute cholecystitis. Recently, even earlier cholecystectomy within 24 hours after hospital admission has been recommended. However, the factors that influence surgical difficulty in this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Furthermore, risk factors evaluated via a presurgical CT scan vary. Among these factors, CT attenuation, 22 absence of gallbladder wall enhancement, presence of a gallstone in the gallbladder infundibulum, 23 edema in the gallbladder wall, 13 and dirty fat signs 24 have been reported. However, to the best of our knowledge, none of the reports indicated that the maximum diameter of the gallbladder measured via a CT scan was a risk factor for difficult LC in patients with AC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, risk factors evaluated via a presurgical CT scan vary. Among these factors, CT attenuation, 22 absence of gallbladder wall enhancement, presence of a gallstone in the gallbladder infundibulum, 23 edema in the gallbladder wall, 13 and dirty fat signs 24 have been reported. However, to the best of our knowledge, none of the reports indicated that the maximum diameter of the gallbladder measured via a CT scan was a risk factor for difficult LC in patients with AC.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with high BMI were having significantly difficulty LC which was also describe in previous studies across the world. [8][9][10][11][12] Further analysis showed that 75% of cases with obesity and all the cases having morbid obese had difficulty LC.…”
Section: Discussionmentioning
confidence: 99%